Penerapan Sanksi Pidana Terhadap Anak Sebagai Pelaku Tindak Pidana Kekerasan Seksual (Studi Putusan PN PAMEKASAN No. 8/Pid.Sus-Anak/2022/PN Pmk) - Moh. Sholehoddin; Rachmat Ihya (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Sexual violence involves forced sexual acts by an adult on a child or a child on another child. This study aims to identify the factors that influence children to commit such crimes, apply a restorative justice approach to child perpetrators of sexual violence, and analyze the court decision at the Pamekasan District Court in case Number: 8/Pid.Sus-Anak/2022 /Pn. Pmk. The method used is a normative juridical approach with a qualitative descriptive approach, as well as data collection through documents and literature studies. Data analysis was carried out following the theory through the stages of condensing data, presenting data, and drawing conclusions or verifying results (Miles et al., 2014). The results of the study show that the factors that influence children to become involved in this crime include the relationship between the perpetrator and the victim that is used by the perpetrator, as well as environmental influences such as isolation or activities without parental supervision. The restorative justice approach is used in dealing with cases of sexual violence against minors. Analysis of the judge's decision in case Number: 8/Pid.Sus-Anak/2022/Pn. Pmk shows the judge sentenced him to one year's prison sentence at Pamekasan Prison and job training at Upt. Contribution to Social Services on Jl. Ronggo Sukowati, Pamekasan Regency for three months.